Interplay between Lactobacillus rhamnosus GG and Candida and the involvement of exopolysaccharides. Issue 6 (3rd August 2017) - Allonsius, Camille N.; van den Broek, Marianne F. L.; De Boeck, Ilke; Kiekens, Shari; Oerlemans, Eline F. M.; Kiekens, Filip; Foubert, Kenn; Vandenheuvel, Dieter; Cos, Paul; Delputte, Peter; Lebeer, Sarah
Summary: A number of clinical studies have shown protective effects of lactobacilli against Candida species in the gastrointestinal tract, the urogenital tract and the oral cavity, while others did not show clear effects. Evidence on the mode of action of lactobacilli against Candida is also still lacking. In this study, the anti‐ Candida activity of the model probiotic strain Lactobacillus rhamnosus GG was explored in different assays to determine molecular interactions. We found that L. rhamnosus GG was able to interfere with Candida growth, morphogenesis and adhesion. These three aspects of Candida 's physiology are all crucial to its opportunistic pathogenesis. In follow‐up assays, we compared the activity of L. rhamnosus GG wild‐type with its exopolysaccharide (EPS)‐deficient mutant and purified EPS to evaluate the involvement of this outer carbohydrate layer. Our data demonstrate that purified EPS can both interfere with hyphal formation and adhesion to epithelial cells, which indicates that EPS is part of a combined molecular mechanism underlying the antihyphal and anti‐adhesion mechanisms of L. rhamnosus GG. Abstract : Our results indicate that model probiotic Lactobacillus rhamnosus GG can interfere with the growth, hyphal formation and adhesion of Candida albicans . Next, we investigated the role of the galactose‐rich exopolysaccharides of LGG and found that they can also inhibit hyphal formation and adhesion of C. albicans .